PENGEMBANGAN MODEL EVALUASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN DI SEKOLAH - Ahmad Jaelani; Aan Hasanah (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
The purpose of this study was to determine the development of character education evaluation models in learning in schools in terms of the nature of students and learning evaluation techniques. The focus of this study regarding the implementation and effectiveness of the use of character education models in schools. In addition, the discussion will be elaborated through the scale of effectiveness, staff perceptions, inventory of school problems, evaluation by the general public, inventory of student behavior, student portfolios, assessing student views, and opinion polls on students' parents. This research method uses literature review and online observation. The results showed that the development of character education evaluation models in learning in schools ran effectively and could be accepted by students at school, thus, the development of character education evaluation models in learning in schools could be used as a model of education in schools.